Impact of Cultivating Environment on the Terms of Persistence and Certain Properties of Cholera Vibrios - S. V. Titova; E. A. Men’shikova; E. M. Kurbatova; L. K. Lysova; I. V. Arkhangel’skaya; O. V. Duvanova; A. V. Mironova; A. V. Samorodova; E. A. Moskvitina (Проблемы особо опасных инфекций, 2016)
Objective of the study is to investigate the impact of cultivating temperature and medium on the terms of persistence, ctx gene retention, and enzymatic activity of V. cholerae O1 with various toxigenicity.Materials and methods. Utilized were the strains of V. cholerae El Tor: P-5879, P-19613, and also the strain P-19787.Results and conclusions. In the process of studying cholera vibrios El Tor with different genetic characteristics it was determined that the longest terms of persistence (19 days) on mineral substrates at 5 ºC were observed for toxigenic strains, while for non-toxigenic ones it made less than 17 days. At the same time cholera vibrios can persist continuously and even reproduce on mineral substrates under the conditions of subnormal lowered temperatures (not less than 10 °C). Toxigenic strains of Vibrio cholerae, irrespectively of cultivating medium and temperature, retained ctx gene in their genome and maintained enzymatic activity throughout the experiment. Such long-term persistence of cholera vibrios at low temperatures on mineral substrates may be regarded as possibility of preservation of V. cholerae toxigenic strains in case of import by the infected persons or vibrio-carriers.